Faktor – Faktor yang berhubungan dengan Kejadian Stunting pada Balita: Literature Review - Soleha, Isti Charoh Amin; Riya, Rosa (Universitas Baiturrahim, 2024)
Stunted toddlers are caused by a lack of parenting styles for toddlers, be it parenting for feeding, parenting for complementary feeding and exclusive breastfeeding. Toddlerhood is a very important period for survival in the future. Therefore, it is necessary to pay attention to health conditions, including the nutritional status of children under five. The problem of stunting has a big impact on the future of toddlers. The aim of the research is to analyze and examine journals related to factors related to stunting in Baita. This research is a quantitative study using the literature review method using the Google Scholar and PubMed databases, study year 2019nc -2022. Using JBI critical appraisal with Quasi-experimental studies. Based on PRISMA, the number of articles obtained was (n = 120349) and articles accepted (n = 7). The results showed various factors that cause stunting in toddlers, namely nutritional status during pregnancy, exclusive breastfeeding, immunization, infection, sanitation, mother's knowledge about stunting and culture, parenting and golden ageh nutrition